Arist. Poet. 1461b1–3: a broad hint at Zoilus? - Pavlova, Anastasija (Philologia Classica, 2019)
In Poetics 25 (1461b1–3), Aristotle mentions critics who tend to misunderstand the text or read it inaccurately and thus criticise not the actual work, but rather their ideas on it. Some of the extant fragments of Zoilus (4th c. BC), the best-known and the most notorious critic of all the Aristotle’s contemporaries, imply that his critique was sometimes based on misreading and misinterpreting of the text so he could be one of those whom Aristotle meant. This article deals with three fragments attributed to Zoilus (two of them are found in the Scholia to the Iliad, the third one is quoted in Ps. Longinus’ De Sublimitate), each containing criticism towards certain passages in Homer’s poems. On closer examination it turns out that all the inconsistencies Zoilus postulated can be explained, should we read the text more carefully. Hence Zoilus dealt not with what is written but rather with what seemed to him to be convenient for his criticism.